TFTIA Table of Contents - TFTIA Co-Chairs (Arctic Council Secretariat, 2016)
Draft table of contents, following 2nd TFTIA meeting, submitted by the Arctic Council Task Force on Telecommunications Infrastructure in the Arctic (TFTIA) to the Senior Arctic Officials meeting in Fairbanks, Alaska, 16-17 March, 2015.